ANALISIS KEBUTUHAN RUANG PARKIR UNTUK FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO KAMPUS TEMBALANG - Eko Ari Purnomo; Atik Purnamasari; Dojoko Purwanto; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Diponegoro University is a State University in Central Java. Faculty of Engineering is part of some faculty at UNDIP. One of the problems from this faculty is parking space requirements. Although it has provided a parking space (off street parking) in each faculty, but in reality there are many vehicles parked on the roadside (on street parking). This final report aims to evaluate the need of existing parking spaces and planned capacity expansion of existing parking spaces. Methodologies used include: field surveys, problem identification, data collection, test of the validity with chi-square test, data analysis, calculation of SRP needs, arrangement of the old park and planning of new park. The number of the current shortage of parking space requirements in Engineering Faculty is 141 SRP for cars and 894 SRP for motorcycles. Meanwhile for the development of the next 5 years is 237 SRP for cars and 1568 SRP for motorcycles. Development of parking area with komunal parking area construction, to join of parking area on Civil Engineering with Geology Engineering, and to join of parking area on Chemistry Engineering, Industry Engineering, Machine Engineering. Also structuring again the parking area configuration on Architek, PWK, Electrical Engineering, and Lecture Together Building. Based on the analysis of the calculation, planning is considered to have been able to solve the needs of today and the parking spaces for the development of the next 5 years is until 2019. To solving the possibility of the occurrence of on-street parking, the solution is given by the installation of parking prohibition signs around the side of the road.